Biomechanical investigation of positive reduction in the femoral neck fracture: a finite element analysis - Zhou, Xiang; Li, Xishan; Böker, Kai Oliver; Schilling, Arndt F.; Lehmann, Wolfgang (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Gotfried positive reduction offers an alternative strategy for femoral neck fracture (FNF) when achieving anatomical reduction is challenging. However, quantifying positive reduction remain unclear. The purpose of this study was to investigate the biomechanical behavior of positive reduction across different Pauwels classification, providing a reference for quantifying positive reduction in clinical practice.Methods: Three-dimensional (3D) models of FNF were established and categorized according to the Pauwels classifications (Pauwels I, II, and III), each of them contained seven models with different reduction qualities, including an anatomical reduction model, two negative reduction models, and four positive reduction models, all of which were stabilized with dynamic hip screws (DHS) and cannulated screws (CS). We investigated the maximal von-Mises stress of internal fixation and proximal femoral, femoral fragment displacement, and maximal von-Mises strain at the proximal fragment fracture site when a 2100N load was applied to the femoral head.The maximum von-Mises stress on the internal fixators in each Pauwels group was lowest in the anatomical reduction model. In the Pauwels I group, positive reduction exceeding 3mm resulted in the maximum von-Mises stress on the internal fixators surpassing that of the negative reduction model.For the Pauwels II group, positive reduction beyond 2mm led to the maximum von-Mises stress on the internal fixators exceeding that of the negative reduction model. In the Pauwels III group, positive reduction beyond 1mm caused the maximum von-Mises stress on the internal fixators to be higher than that of the negative reduction model. The maximum von-Mises strain at the fracture site of proximal femur fragment increased with positive reduction. Varus displacement increased in positive reduction models as the Pauwels angle rose, potentially exacerbating rotation deformity in Pauwels III group.Excessive positive reduction may increase the risk of FNF failure after internal fixation.From a biomechanical stability perspective, positive reduction should be limited to 3mm or below in the Pauwels I group, restricted to not exceed 2mm in the Pauwels II group, and should not exceed 1mm in the Pauwels III group. Negative reduction should be avoided in all Pauwels groups.